2022
DOI: 10.1002/jcb.30303
|View full text |Cite
|
Sign up to set email alerts
|

The activation of M2 muscarinic receptor inhibits cell growth and survival in human epithelial ovarian carcinoma

Abstract: Ovarian cancer is the fifth leading cause of cancer-related deaths in females.Many ovarian tumor cell lines express muscarinic receptors (mAChRs), and their expression is correlated with reduced survival of patients. We have characterized the expression of mAChRs in two human ovarian carcinoma cell lines (SKOV-3, TOV-21G) and two immortalized ovarian surface epithelium cell lines (iOSE-120, iOSE-398). Among the five subtypes of mAChRs (M1-M5 receptors), we focused our attention on the M2 receptor, which is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Over the past decade, various studies have shown that the activation of mAChRs is critical in the regulation of cell proliferation and cancer progression [ 43 ]. In this context, we have been studying the role of the M2 mAChR in cancer for many years, demonstrating that activation of this receptor subtype brings about anti-proliferative and cytotoxic effects on cells of different tumor types such as ovarian cancer [ 19 ], breast cancer [ 18 ], neuroblastoma [ 21 ] and GBM [ 32 ]. For GBM, we showed that in the U251 cell line, the activation of M2 mAChRs by the orthosteric agonist APE caused cell cycle arrest as well as progressive accumulation of the cells in the G2/M phase [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, various studies have shown that the activation of mAChRs is critical in the regulation of cell proliferation and cancer progression [ 43 ]. In this context, we have been studying the role of the M2 mAChR in cancer for many years, demonstrating that activation of this receptor subtype brings about anti-proliferative and cytotoxic effects on cells of different tumor types such as ovarian cancer [ 19 ], breast cancer [ 18 ], neuroblastoma [ 21 ] and GBM [ 32 ]. For GBM, we showed that in the U251 cell line, the activation of M2 mAChRs by the orthosteric agonist APE caused cell cycle arrest as well as progressive accumulation of the cells in the G2/M phase [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…mAChRs are G protein-coupled receptors (GPCRs) involved in the regulation of several fundamental processes in both central and peripheral nervous systems [ 17 ]. Moreover, the expression of mAChRs in different tumors and their strategic role in the modulation of cancer cell proliferation, survival and migration have been demonstrated [ 18 , 19 , 20 , 21 , 22 ]. In this framework, we have demonstrated that the activation of M2 mAChR by the orthosteric M2 agonist Arecaidine Propargyl Ester (APE) has negative effects on cell proliferation and survival, both in GBM cell lines and in GBM cancer stem cells (GSCs) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will focus on mAChRs. As an example, the recent translational research of human epithelial ovarian carcinoma have described the role of M 2 mAChRs in M 2 cell growth and survival ( Taggi et al, 2022 ). The authors have used arecaidine propargyl ester as M 2 mAChR preferential agonist.…”
Section: Introductionmentioning
confidence: 99%